Pengaruh Integrasi Untuk Mengurangi Resiko Pada Pertumbuhan Wilayah Provinsi Aceh - Achmad Faris Fizabillah; Yuyun Setyawati; Tina Safira; Muhammad Yasin (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
Regional growth centers assume the ability to integrate as many development interests as possible among those with an interest in development. Thus, regional growth centers also mean qualitative development and/or growth. Theoretically and empirically, inclusive economic growth is closely related to regional development. The existence of sub-regions in Aceh needs special attention, in order to develop the concept of regions as centers of development. During the New Order era, the concept of regional development was apparently renewed.